(untitled) (Andamios, Revista de Investigación Social, 2007)
The process of globalization has taken place along with a strengthening of identities. This article features a defense of the rights of the person. These rights are ethical achievements to be defended inside liberal societies, and also in traditional cultures. Three theoretical positions are posed: the first is to impose liberal ideals to societies that are not liberal; the second is to accept the lifestyle of each group whenever it respect human rights; the third is not only to accept diversity, but also to encourage it. The state has to protect minority cultures through special policies, but they can’t favor minorities in which there aren´t basic equality or basic rights.